A comparison of total cost estimates between exclusive breast-feeding and breast milk substitute usage in humanitarian contexts - Zoe Katherine Mowl; Amnesty LeFevre; Mija Ververs (Cambridge University Press, 2023)
Abstract Objective: Using a model-based analysis, we calculated the total costs associated with the exclusive breast-feeding (EBF) and breast milk substitute (BMS) usage for one infant for six months within select humanitarian contexts to (a) determine if there is a notable difference in costs and (b) use these results to inform future creation of data-informed humanitarian response standard operating procedures. Design: The inputs and costing data were drawn from a mixture of local e-commerce vendors, peer-reviewed literature and personal communications with field-based humanitarian responders. To account for cost fluctuations, each input's costs along with low and high parameters are presented. All costs are presented in 2021 United States Dollars. Setting: Humanitarian responses within Indonesia and Jordan. Participants: Not applicable. Results: There was a notable difference in the total cost of care in both selected locations across the study arms (Indonesia: $542; Jordan: $892). Conclusions: Given the reality of limited funding for comprehensive humanitarian response around the world and the necessity of prioritising certain interventions, humanitarian response organisations should consider the notable cost difference between EBF and BMS usage (along with the proven health benefits of EBF). This difference should play a role in informing the future creation of standard operating procedures while also ensuring that all infants within a humanitarian crisis receive appropriate feeding.